An investigation of Korean consumers service quality perception of imported retail services: Implications of consumer ethnocentrism - Eunji Oh; Jiwon Lee; M. Minsuk Shin (Global Business & Finance Review (GBFR), 2020)
Purpose: This study analyzes how consumers' level of ethnocentrism influences their perceived quality on an imported service. Design/methodology/approach: In order to do so, this study firstly utilizes five measurement items to assess consumers' level of ethnocentrism. Then, SERVQUAL (Tangibles, Reliability, Responsiveness, Assurance, and Empathy) is employed to evaluate consumers' perceived quality on the imported service. Lastly, consumers' level of ethnocentrism and their evaluation on the imported service is comparatively analyzed in order to identify the relationship between the ethnocentric customers and their evaluation on the service. Starbucks was used as the sample of an imported service. The data was collected from general Korean consumers and a total of 220 respondents participated in the survey. Findings: As a result, Reliability, Responsiveness, and Empathy factors were empirically proved to have significant relationship between consumer's ethnocentrism and consumer's perceived quality of the imported service. Based on the results, this study suggests focusing on localization of Reliability, Responsiveness, and Empathy factors when an international company expands their market to the countries with high tendency of ethnocentrism, such as: South Korea, China and the United States of America. Research limitations/implications: The sample size that was used for this study is rather small and the survey was conducted and analyzed in relatively short time period. Also, if traditional Korean coffee shops can be compared to as Starbucks in the future study, more meaningful result will be drawn. Originality/value: By demonstrating that ethnocentrism influences consumers' purchase intentions in the decision-making process through Reliability, Responsiveness, and Empathy, this study re-emphasizes the importance of localization when expanding services to countries with high levels of ethnocentrism.
Keywords: 650; Consumer Behavior; Imported Retail Service; Consumer Ethnocentrism (CET); Service Quality; SERVQUAL